Induced variation in BRASSINOSTEROID INSENSITIVE 1 (BRI1) confers a compact wheat architecture - Manpartik S. Gill; Andrew L. Phillips; Danuše Tarkowská; John Addy; Patrycja Sokolowska; M. John Foulkes; Stephen Pearce; Stephen G. Thomas; Peter Hedden (BMC Plant Biology)
Abstract Background The brassinosteroid (BR) plant hormones regulate numerous developmental processes, including those determining stem height, leaf angle, and grain size that have agronomic relevance in cereals. Indeed, barley (Hordeum vulgare) varieties containing uzu alleles that impair BR perception through mutations in the BR receptor BRASSINOSTEROID INSENSITIVE 1 (BRI1) exhibit a semi-dwarf growth habit and more upright leaves suitable for high-density planting. We used forward and reverse genetic approaches to develop novel BRI1 alleles in wheat (Triticum aestivum L.) and investigated their potential for crop productivity improvement. Results The combination of ethyl methanesulfonate-induced mutations introducing premature stop codons in all three homoeologous TaBRI1 genes resulted in severe dwarfism, malformed leaves and sterility as observed in bri1 mutants in other species. Double mutants had reduced flag-leaf angles (FLAs) conferring a more upright canopy but exhibited no differences in height or grain weight. In a targeted forward genetics screen using a double mutant, we identified two BR-insensitive lines with reduced height and FLA that contained amino acid substitutions in conserved regions of BRI-A1. The less severe mutant had a 56% reduction in FLA and was 35% shorter than the wild type, although seed set, seed area and grain weights were also reduced. The most severe mutants contained elevated levels of bioactive BRs and increased expression of BR-biosynthesis genes consistent with reduced feedback suppression of biosynthesis. Conclusion Our study gives a better understanding of BRI1 function in wheat and provides mutants that could potentially be explored for improving grain yields when sown at high density.